Karakteristik Mikroplastik pada Sedimen dan Air laut di Muara Sungai Wulan Demak - Nando Arta Gusti Pamungkas; Retno Hartati; Sri Redjeki; Ita Riniatsih; Jusup Suprijanto; Edy Supriyo; Widianingsih Widianingsih (Jurnal Kelautan Tropis, 2022)
Microplastics are small plastic particles that have the characteristics of easily accumulating in seawater and sediments with a diameter of less than 5 mm. The presence of microplastics in seawater and sediments may have a chain impact on marine ecosystems and humans. The purpose of this study was to determine the characteristics of microplastics in sediment and seawater in the Wulan River Estuary, Demak. Sediment and seawater samples were taken by purposive sampling at five different stations in line with the river mouth on 20 May 2021. Visual identification and counting of microplastics using a microscope, and FTIR (Fourier transform infrared) test. The highest abundance of microplastics was found in Station 2 sediment (400 particles.Kg-1) and Station 1 seawater (99 particles.L-1) which is the end of the Wulan river flow. The diversity of microplastic characteristics in the form of fragments, fibers, pellets and films, the most abundance was fragments of particles in sediment and seawater samples. The color of the microplastic particles is predominantly black and blue, with lesser number of brown, white, red, green, yellow and purple. The microplastic particle size range was found between 1.00-259.06 m. Microplastic pollutants are nitrile, nylon and PTFE (Polytetrafluoroethylene) plastics. The results of this study reveal the sources of anthropogenic pollution in the study area which are not only caused by human activities on land but also from the movement of water in the marine environment.  Mikroplastik adalah partikel plastik kecil yang memiliki karakteristik mudah terakumulasi pada air laut laut dan sedimen dengan ukuran diameter kurang dari 5 mm. Keberadaan mikroplastik pada air laut laut dan sedimen dapat memberikan dampak berantai terhadap ekosistem perair lautan dan manusia. Tujuan dari penelitian ini adalah untuk mengetahui karakteristik mikroplastik pada sedimen dan air laut di Muara Sungai Wulan, Demak. Sampel sedimen dan air laut diambil dengan purpossive sampling di lima stasiun yang berbeda segaris dengan muara sungai pada tanggal 20 Mei 2021. Identifikasi dan penghitungan mikroplastik secara visual menggunakan mikroskop, dan uji FTIR (Fourier transform infrared). Kelimpahan mikroplastik tertinggi ditemukan pada sedimen Stasiun 2 (400 partikel.Kg-1) dan air laut Stasiun 1 (99 partikel.L-1) yang merupakan akhir dari aliran sungai Wulan. Keragaman karakteristik mikroplastik yang berupa fragment, fiber, pellet dan film, partikel fragmen terbanyak di sample sedimen dan air laut. Warna partikel mikroplastik didominasi hitam dan biru, dengan warna coklat, putih, merah, hijau, kuning dan ungu yang lebih sedikit.  Rentang ukuran partikel mikroplastik yang ditemukan antara 1,00-259,06 µm. Polutan mikroplastik berjenis plastik nitrile, nylon dan PTFE (Polytetrafluoroethylene). Hasil penelitian ini mengungkapkan sumber polusi antropogenik di daerah penelitian yang tidak hanya disebabkan oleh aktivitas manusia di darat tetapi juga dari pergerakan air di lingkungan laut.